Eksplorasi Material Alternatif dalam Pembuatan Puppet dan Set untuk Produksi Animasi Stop-Motion Berjudul “Junk Food” - Dominika Anggraeni Purwaningsih (Universitas Multimedia Nusantara, 2021)
Traditional stop-motion animated films have unique visual characteristics so that they have many fans, but the number of stop-motion filmmakers is actually very minimal. This is understandable because compared to other animation techniques that are done digitally, stop-motion seems impractical because it requires longer time, higher production costs, and more tools and materials. This paper discusses the exploration and utilization of alternative materials from well-known conventional materials in making puppets and sets for stop-motion animation. The alternative materials in question will use used goods, household inorganic waste, and other reusable materials while still paying attention to function and aesthetics so as to contribute to waste recycling. This is in line with the theme of the film “Junk Food” which raises the issue of environmental pollution, where the results of this research will be applied. This qualitative research is project-based and uses literature study, observation, and experiment methods to collect data. The results of this research are up to the stage of making 2 puppets and 2 sets to answer the problem of exploring alternative materials from used goods. Keywords: stop-motion animation, puppet, set, alternative materials